The validation of new formula of islamic home financing among finance expertise - Puspa Liza, Ghazali; Nik Hazimi, Mohammed Foziah; Lazim, Omar; Jaafar, S.A.S; Razak, R.A; Sukono, .; Bon, A.T. (2019)
Islamic banks in Malaysia practiced a different type of shariah principle that may offer advantage and disadvantages to Islamic home financing's customer. Instead of analyzing the percentage of acceptance to Barakah Model Islamic home financing among public, a set of questionnaire were distributed among Islamic financial expertise. Barakah model need to be validate as to check it is fit according to Islamic finance's need or not. The Barakah model is design to cater the lower income earners especially RM3500 and below with extra benefit to protect the house owner if anything happen in future